Detection of SARS-CoV-2 in Saliva and Nasopharyngeal Swabs According to Viral Variants - Maud Salmona; Marie-Laure Chaix; Linda Feghoul; Nadia Mahjoub; Sarah Maylin; Nathalie Schnepf; Hervé Jacquier; Eve-Marie Walle; Marion Helary; Guillaume Mellon; Nathalie Osinski; Widad Zebiche; et al. (Microbiology Spectrum, 2022)
ABSTRACT The genome of the Omicron variant of concern (VOC) contains more than 50 mutations, many of which have been associated with increased transmissibility, differing disease severity, and the potential to elute immune responses acquired after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination or infection with previous VOCs. Due to a better tropism for the upper respiratory tract, it was suggested that the detection of the Omicron variant could be preferred in saliva, compared to nasopharyngeal swabs (NPS). Our objective was to compare the SARS-CoV-2 levels in saliva fluid and NPS to estimated Ct values, according to the main SARS-CoV-2 variants circulating in France since the beginning of 2021. We analyzed 1,289 positive reverse transcription-polymerase chain reaction (RT-PCR) results during the three major waves: Alpha, Delta, and Omicron. NPS and saliva sampling were performed for 909 (71%) and 380 (29%) cases, respectively. The Ct values were significantly lower in the NPS samples than in the saliva samples for the three main VOCs. Still, the difference was less pronounced with the Omicron variant than for the Alpha and Delta variants. In contrast, in the saliva samples, Ct values were significantly lower for the Omicron variant than for the Delta (difference of −2.7 Ct) and the Alpha (difference of −3.0 Ct) variants, confirming a higher viral load in saliva. To conclude, the higher viral load in saliva was evidenced for the Omicron variant, compared to the Alpha and Delta variants, suggesting that established diagnostic methods might require revalidation with the emergence of novel variants. IMPORTANCE Established methods for SARS-CoV-2 diagnostics might require revalidation with the emergence of novel variants. This is important for screening strategy programs and for the investigation of the characteristics of new variants in terms of tropism modification and increased viral burden leading to its spread. SARS-CoV-2 RT-PCR screening on saliva samples reported lower but acceptable performance, compared to nasopharyngeal samples. Due to a better tropism for the upper respiratory tract, it was suggested that the detection of the Omicron variant could be preferred in saliva, compared to nasopharyngeal swabs. Our study analyzed 1,289 positive RT-PCR results during the three major waves in France: Alpha, Delta, and Omicron. Our findings also showed a higher viral load in saliva for the Omicron variant, compared to the Alpha and Delta variants.